Indonesia Economic Quarterly, January 2017 : Sustaining Reform Momentum - World Bank (World Bank, Jakarta, 2017)
This Indonesia Economic Quarterly (IEQ) reports on the key developments over the past three months in Indonesia's economy as on January 2017. The return of global policy uncertainty and financial market volatility represent risks to Indonesia’s growth outlook. However, Indonesia’s recent economic performance and policy reforms can help weather these risks. Gross domestic product (GDP) growth eased in third quarter as government consumption fell. The current account deficit narrowed and direct investment was strong in third quarter. Domestic financial conditions remain robust despite recent global headwinds. Fiscal policy credibility was enhanced through expenditure cuts in 2016 and more realistic revenue targets in the approved 2017 Budget. Baseline projections for real GDP growth remain at 5.1 percent for 2016 and 5.3 percent in 2017. Improving the quality of public spending is critical for Indonesia to achieve its development goals in the short to medium term. Student-centered teaching practices result in better student learning outcomes.